PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN, DAN EFEKTIVITAS KOMITE AUDIT TERHADAP TIMELINESS - Lea Amanda Sari; Hesty Ervianni Zulaecha; Hamdani, Hamdani; Daniel Rahandri (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the effect of profitability, ownership structure, effectiveness, and size of the audit committee company on timeliness of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). The research year period used is 4 years, namely the 2016-2021 period. The population of this study includes all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). The sampling technique used a population sampling technique based on the established criteria obtained 17 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used is panel data regression analysis. The results of the study simultaneously show that the profitability, ownership structure, effectiveness, and firm size of the audit committee on timeliness. The results of the study partially show that profitability has a significant effect on timeliness, ownership structure, effectiveness, the size of the audit committee company has no significant effect on timeliness.